DAMPAK PENERAPAN PSAK 73 ATAS SEWA TERHADAP KINERJA KEUANGAN PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Siregar, Dina Khairuna (LPPM Universitas Bina Bangsa, 2023)
PSAK 73 on leases will come into effect in Indonesia in 2020 which is the adoption of IFRS 16 Leases which replaces PSAK 30. PSAK 73 requires companies to record leases as finance leases. This study aims to determine the impact of implementing PSAK 73 on the financial performance of LQ45 companies listed on the IDX for the 2019-2020 period. This study aims to examine differences in debt structure and company profitability before and after the implementation of PSAK 73. The method used is descriptive comparative method with a quantitative approach.. The data used is the LQ45 company financial statements with a population of 45 companies and based on purposive sampling selected 38 companies as samples. The results of this study showed that the debt structure of LQ45 companies from the DAR and DER ratios did not have significant changes before and after the implementation of PSAK 73, while the profitability of LQ45 companies seen from the ratios of ROA and ROE had significant changes before and after the implementation of PSAK 73